A localized surface protein of guinea pig sperm exhibits free diffusion in its domain (The Rockefeller University Press, 1984)
Using the technique of fluorescence redistribution after photobleaching, we are studying the cellular mechanisms involved in localizing surface molecules to particular domains. A number of antigens localized to discrete surface regions have been identified with monoclonal antibodies on guinea pig sperm cells ( Primakoff , P., and D. G. Myles , 1983, Dev. Biol., 98:417-428). One of these monoclonal antibodies, PT-1, binds exclusively to the posterior tail region of the sperm cell surface. PT-1 recognizes an integral membrane protein that in complex with n-octyl-beta-D-glucopyranoside has a sedimentation coefficient of 6.8S in sucrose density gradients. Fluorescence redistribution after photobleaching measurements reveal that within its surface domain the PT-1 antigen diffuses rapidly (D = 2.5 X 10(-9) cm2/s) and completely (greater than 90% recovery after bleaching). These results rule out for this membrane protein all models that invoke immobilization as a mechanism for maintaining localization. We propose that the mechanism for localization of the PT-1 antigen may be a barrier to diffusion at the domain boundary.